Pengaruh Manajemen Laba, Profitabilitas, dan Struktur Modal Terhadap Nilai Perusahaan Dimoderasi Kebijakan Dividen - Apriadi, Riyan; Setijaningsih, Herlin Tundjung (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This research analyzes the effect of earnings management, profitability, and capital structure on firm value, using dividend policy as a moderating variable. Data was collected through annual financial reports of manufacturing companies listed on the Indonesian Stock Exchange. The data was processed using the E-views 12 program. This research indicates that earnings management has no effect on firm value. Profitability has a positive effect on firm value without moderation. However, when there is moderation in dividend policy, profitability has no effect. Capital structure has a negative effect on firm value without moderation. When there is moderation in dividend policy, capital structure has no effect. Dividend policy can moderate the effect of earnings management, but strengthens the effect of profitability, and weakens the effect of capital structure on firm value. The research results can be used to make decisions regarding financial and investment strategies